THE RELATIONSHIP BETWEEN LEARNING ACTIVITIES AND INITIAL ABILITIES WITH STUDENT LEARNING OUTCOMES AT BUILDING ENGINEERING EDUCATION - metsidaud, metsidaud (Jurnal Teknologi Pendidikan, 2023)
This study aims to analyze: (1) the relationship between learning activities and learning outcomes of building engineering education students, (2) the relationship between initial abilities and learning outcomes of building engineering education students, and (3) the relationship between learning activities and initial abilities simultaneously with learning outcomes. The study by building engineering education students. The design of this study is quantitative research with a correlational research approach. From the results of the study: 1) there is a significant relationship between learning activities and learning outcomes, contributing 21.62%; 2) there is a significant relationship between initial ability and learning outcomes, giving a contribution of 37.09%; 3) there is a significant relationship between learning activities and initial abilities simultaneously with learning outcomes, giving a contribution of 46,20%. Thus that increased learning activities, and conducive initial abilities are expected to be able to provide maximum learning outcomes for students. In other words, with learning activities, high initial abilities will foster good and high student learning outcomes